Does Air Quality Health Index (AQHI) Forecasting Improve Population Health? Evidence from Hong Kong, China - Yilin Chen; Bibo Yin (Sustainability, 2026)
The implementation of the Air Quality Health Index (AQHI) is a regional climate action intended to protect population health, but its empirical linkage to the sustainability goal of good health and well-being remains untested. Using mortality data from Hong Kong (2013–2022), we employed a two-month-lag fixed-effects model to estimate the change in years of life lost (YLL) associated with monthly AQHI warning frequency. We further assessed heterogeneity across demographic and geographic subgroups, and explored the underlying mechanisms. The findings show that monthly AQHI warning frequency is negatively associated with YLL two months later. Each additional warning per month is associated with a reduction of 0.0032 units (SE = 0.0011) in per capita YLL across districts in Hong Kong. The baseline result was further supported by extended survival analyses. Heterogeneity analyses showed that each additional AQHI warning was associated with a significant reduction in YLL among males (coef. = −0.0066, SE = 0.0001) and those with spouses (coef. = −0.0065, SE = 0.0083), but not among females or those without spouses. Mechanism analyses suggested that the effect of AQHI warning frequency on YLL reduction was significantly moderated by individual behavioral responses, including increased face mask usage (int. coef. = −0.0047, SE = 0.0016) and reduced short-term travel (int. coef.= −0.0069, SE = 0.0004), and through socio-environmental pathways such as reduced traffic accidents (int. coef. = −0.0134, SE = 0.0034) and lower carbon emissions (int. coef. = −0.0367, SE = 0.0112). Hong Kong’s AQHI forecasting experience demonstrates the viability of health risk warnings as a climate adaptation strategy in sustainable urban governance, while its observed equity gaps offer critical lessons for refining inclusive environmental health policies.